PENGARUH LINGKUNGAN SEKOLAH, PERAN GURU DAN MINAT BELAJAR SISWA TERHADAP MOTIVASI BELAJAR PENJAS SD INPRES BUTTATIANANG I MAKASSAR - SYAMSUL DARMAWAN (Jurnal Muara Pendidikan, 2018)
The objective of this study was to find out the effect of the school environment, the role of teachers and the Students Learning Interest on the Motivating to Learn Physical Education and Health Sciences at Elementary School InpresButtatianang I of Makassar. The type of this research is descriptive analysis with research design using Path Analysis. The population is the fifth grade students Elementary School InpresButtatianang I of Makassar. There are 28 students. The technique to determining the sample is in a population that is affordable. The data analysis technique used was descriptive analysis by using SPSS 18 for windows. The results of this study indicated that (1) Elementary School InpresButtatianang I of Makassar, has a direct influence on school environment that is significant to students' learning interest on the Physical Education and Health Sciences amount 40.26%. (2) the direct influence of the teacher's significant role in student learning interest on Physical Education and Health Sciences amount 31.36%. (3) the influence of school environment in student learning motivation on Physical Education and Health Sciences subjects amount 9.48%. (4) the direct influence of the teacher's role in student motivation on Physical Education and Health Sciences subjects amount 63.04%. (5) the influence of learning interest in student learning motivation on Physical Education and Health Sciences amount 24.32%. (6) the influence of school environment in student learning motivation on Physical Education and Health Sciences through learning interest amount 77.88%. (7) the influence of teacher's role in students' learning motivation on Physical Education and Health Sciences subjects through learning interest amount 77.88%.